Model Konseptual Modul Pembelajaran Berkelanjutan pada Konsentrasi Keahlian Desain dan Produksi Busana di SMK - Yuvila Rizky Dwi Arta; Isnandar; Syarif Suhartadi (LPPM Institut Pendidikan Nusantara Global, 2026)
Vocational learning in vocational high schools requires the integration of conceptual competence, practical skills, and work readiness aligned with industry needs. However, learning in the Fashion Design and Production specialization still faces challenges related to the gap between learning materials, industrial development, and the implementation of competency-based assessment. In addition, practical learning activities are often oriented toward product completion without continuous reflection and evaluation. This study aims to formulate a conceptual model of a sustainable learning module for productive subjects in the Fashion Design and Production specialization. The study employed a literature review method with a descriptive qualitative approach through the analysis of reputable international journals, academic books, and relevant educational policy documents. The findings indicate that a sustainable learning module designed through a cycle of needs analysis, product planning, production practice, authentic assessment, reflection, feedback, and gradual quality improvement can enhance the quality of vocational learning. The integration of digital technology, authentic assessment, and sustainable fashion principles becomes an essential component in module development. The proposed model is adaptive and oriented toward the gradual improvement of students’ practical work quality in accordance with industry demands.